Valuation, Capital Structure, and Shareholder Unanimity for Depository Financial Intermediaries - SEALEY, C. W. (Journal of Finance, 1983)
ABSTRACT The theory of corporate finance is not directly applicable to financial intermediary decision‐making. The lack of applicability stems largely from the particular conditions that distinguish intermediary operations from those of the nonfinancial firm. First, when intermediaries accept deposit financing, they must produce services such as liquidity and convenience at considerable expense for real resources. Second, the introduction of intermediation is likely to be accompanied by incomplete markets so that shareholder unanimity is not in general valid. In this paper, a model with incomplete markets is developed and a shareholder approved rule for intermediary capital structure decisions is derived.